THE ROLE OF CUSTOMER SATISFACTION AS A MEDIATOR IN THE EFFECT OF RELATIONAL MARKETING PRACTICES ON CUSTOMER RETENTION: A CASE STUDY ON XL HOME CUSTOMERS IN MAKASSAR - Nurul Fadilah Aswar (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the relationship between customer retention, customer satisfaction, and relational marketing practices in XL Home users in Makassar who have used the service for at least one year. Purposive sampling method is used to select 100 respondents who meet these criteria. The data collected were analyzed using Structural Equation Model (SEM) with SMART PLS program. The results showed that customer satisfaction has a significant effect on customer retention. So is the practice of relational marketing, which also has a significant influence on customer retention and customer satisfaction. In addition, there are indirect effects of relational marketing practices on customer retention mediated by customer satisfaction.